The Language as the Mirror of Selfidentity (the Old Believers in Lithuania Speak about Themselves) - Sinočkina, Birutė (Respectus Philologicus, 2002)
The analysis of the verbal material belonging to the dialects spoken by the Old Believers in Lithuania permits us to draw certain conclusions pertaining to the degree of self identification of those people who live in the surroundings of different languages and different religious creeds. Basing our conclusions on the records of their speech, we can determine that they are conscious of their difference from the local Russians belonging to the Russian Orthodox Church as well as from the Russians living in Russia. Conscious of the specificity of their dialect, the Old Believers are inclined to connect their way of speech with their loyalty to the old forms of religious faith as well as to the traditional forms of life and to their attempts to protect all that their ancestors have bequeathed to them. The synonyms current in the dialect of the Old Believers form binary pairs such as old / new, one's own / belonging to strangers, simple / learned, rural / urban, etc.
Keywords: -